Addressing Environmental Concerns: Strategies of Islamic Boarding School Teachers in Promoting Environmental Ethics - Nur Asiah Jamilah; Muhammad Widodo; Endi Suhendi (International Journal of Nusantara Islam, 2023)
The imperative of instilling environmental ethics in educational institutions has never been more pressing in the face of global environmental challenges. Nurul Iman Islamic Boarding School presents a unique case study in the successful integration of environmental love ethics within its pedagogical framework. This research employed a qualitative approach, utilizing observation, interviews, and document analysis to explore the strategies used by teachers at Nurul Iman Islamic Boarding School. The focus was on understanding how environmental ethics are taught and practiced within the Pesantren setting. The study examined the methods of modeling, habituation, punishment, and lecturing, analyzing how each contributes to the overall objective of fostering environmental consciousness among students. The findings reveal that modeling by teachers plays a critical role in setting a behavioral standard for students. Habituation methods, such as daily duty rosters and community service activities, effectively inculcate routine environmental practices. The punishment method, while used sparingly, effectively reinforces the importance of adhering to environmental standards. Lectures, particularly those grounded in religious texts, provide a theoretical and moral basis for environmental ethics. The integration of these methods has led to a comprehensive approach to environmental education, with students demonstrating a deeper understanding and commitment to environmental stewardship. The study underscores the potential of religious and ethical teachings in shaping environmental attitudes and behaviors, highlighting the importance of a holistic approach to environmental education.